IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROYEK DALAM MENINGKATKAN MOTIVASI DAN PARTISIPASI MAHASISWA PADA PEMBELAJARAN BOLAVOLI - Syaiful, Andi; Muhaemin M, Ince Abdul; Hakim, Nurwahidin (Dharmas Journal of Sport, 2026)
This study aims to analyze the effect of Project-Based Learning (PjBL) on students' motivation and participation in volleyball learning. The research used a quasi-experimental design with a pretest–posttest control group pattern. Subjects consisted of 60 Physical Education students at Cenderawasih University, divided into an experimental group (n=30) and a control group (n=30). Data collection instruments included motivation questionnaires and participation observation sheets. Data were analyzed through normality tests, homogeneity tests, paired t-tests, independent t-tests, and Pearson correlation. Results showed that PjBL significantly increased student motivation from a mean of 3.10 to 4.25 (t=9.87; p<0.001; d≈1.10) and participation from 68% to 88.5% (t=10.12; p<0.001; d≈1.20). Between-group comparisons showed significant differences in both motivation (t=8.45; p<0.001) and participation (t=7.96; p<0.001). Pearson correlation revealed a moderate–strong positive relationship between motivation and participation (r=0.65; p<0.01). These findings indicate that PjBL is effective in increasing student engagement, aligned with the Merdeka Belajar–Kampus Merdeka principles. This model is recommended as a learning strategy for team sports courses.